CAR T expansion and systemic inflammation: diverging impacts on large B-cell lymphoma therapy in the multicenter CART SIE study - Martina Magni; Sadhana Jonnalagadda; Francesca Bonifazi; Massimiliano Bonafe; Silva Ljevar; Giada Zanirato; Serena De Matteis; Federico Stella; Angelica Barone; Giulia Bertolini; Anisa Bermema; Annalisa Chiappella; et al. (Haematologica)
CAR T expansion has been linked to anti-tumor response in relapsed/refractory large B-cell lymphoma both in clinical trials and smaller real-world studies. Here, we present the largest multicenter real-world analysis to date, evaluating 262 patients treated with tisagenlecleucel or axicabtagene ciloleucel in second or subsequent relapse. Our findings underscore the complementary roles of multiparameter flow cytometry (MFC) and droplet digital PCR (ddPCR) in monitoring CAR T cells. While ddPCR accurately quantifies transgene copies, MFC provides critical phenotypic details, revealing CAR T-cell subpopulations that are associated with its efficacy.